9-Alkenylcarbazoles; 10; 13C NMR spectra of 9-vinyl- and cis- and trans-9-propenylcarbazoles; Chemistry of Heterocyclic Compounds; Vol. 18, iss. 2 - Filimonov V. D. Viktor Dmitrievich (1982, 1982)
Title screen